DEMOCRATIC LEADERSHIP SYSTEM TO PURSUIT THE VISION, MISSION, AND GOALS OF COMMUNITY DEVELOPMENT - Sulismadi, S; winarsih, siti nurul fitria (Jurnal Partisipatoris, 2020)
The role of the rural village government in organizing their people to participate inthe development program is the success measurement of community development.A democratic leader views his role as both coordinator and integrator, puttinghimself to control, manage, and supervise his region without precluding the people?sright to express their ideas. This study aims at explaining the people?s responsestowards unsuccessful infrastructure development by their leader and the village?sgovernment. This study reviewed the phenomena using the qualitative approach;the data analysis used descriptive method to analyze the data. An active roleof the society in the infrastructure development shows the concern on the localenvironment. The emergence of activity whose primary purpose is to initiateinfrastructure development such as road and bridge can provide advantages for thelocal people and maintain a good relation among those people.